PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI KEBIJAKAN PENGEMBANGAN DESA WISATA DI KABUPATEN SLEMAN - Nugroho, Dewanto Tri (JURNAL NASIONAL PARIWISATA, 2013)
The study was conducted in the village of Tanjung. Data on rural tourism development policies many writers get in the Department of Culture and Tourism Sleman regency (Official Culture and Tourism Department, Sleman Regency). Interview, observation and documentation study is a method used to collect data. Data processing is performed after the data is collected, and then do the sorting and grouping. Narrative data was to then draw conclusions.Sleman regency has an area of 57,482 hectares or 574.82 km2, which covers 18% of the total land area of Yogyakarta Special Province (Sleman in Figures, 2008).Â Tanjung is living proof that the policies and programs designed by the Department of Culture and Tourism of Sleman district run smoothly and give effect to the level of empowerment. Increased participation and institutional manager rural tourism to be one indication of this. Additional revenue from the economic to the most in the spotlight when the business development of community- based tourism enterprises is discussed. Besides the construction of various infrastructure/public facilities and social well become one of the successful development of locality based community and the uniqueness of a typical community.Â